UNDERSTANDING INTENTION OF GENERATION Z TO REDUCE FOOD WASTE IN INDONESIA: A STUDY INTEGRATING THEORY OF PLANNED BEHAVIOR AND INDIGENOUS CULTURAL VALUES - Alfianto, Yogi Fahreza; Wibowo, Mas Wahyu (Universitas Mercu Buana, 2025)
Food waste has become an urgent global concern, with Indonesia facing notable economic, environmental, and social consequences. The present study examined the determinants of Generation Z’s intention to curb food waste in Indonesia using the Theory of Planned Behavior (TPB), which emphasizes attitudes, subjective norms, and perceived behavioral control. In addition, the research integrated indigenous cultural values, particularly religious and traditional values. Using a quantitative correlational approach, data were obtained from 200 respondents through purposive non-probability sampling. The analysis was performed using Structural Equation Modeling (SEM) via the Partial Least Squares (PLS) method. The results revealed that attitudes, perceived behavioral control, religious values, and traditional values significantly and positively influenced food waste reduction intention. Conversely, subjective norms were found to have no significant effect. These findings highlight that personal beliefs, self-regulation, and cultural values are more influential than social pressure in driving food waste reduction behaviors among Indonesian Generation Z.